Short Term Outcomes of Laparoscopic Versus Open Appendicectomy in Patients with Acute Appendicitis - Parvin, Monika; Chowdhury, Dewan Ali Hassan; Bahar, Mohammad Ashik Anwar (Community Based Medical Journal, 2023)
A prospective, observational study was carried out in the Department of Surgery of Sylhet MAG Osmani Medical College, Bangladesh, from May 2019 to May 2020, to compare the short-term outcomes of laparoscopic versus open appendectomy for acute appendicitis. A total of 120 patients who were diagnosed with acute appendicitis and underwent surgery were included in this study. The selected patients underwent appendectomy either by laparoscopic or using open method under general anesthesia. The patients were divided into two groups – 60 patients underwent laparoscopic appendectomy as group-I and the other 60 patients underwent open appendectomy as group-II. The mean age was 26.25±7.83 years in group-I and 22.88±6.92 years in group-II. The difference was statistically significant (P<0.05). Male predominance was found: 40(66.67%) in group-I and 44(73.33%) in group-II. However, the difference was not statistically significant (P>0.05). The mean operating time was 65.05±8.76 min in group-I and 40.08±4.82 min in group-II. The mean time resumption of diet was 7.3±0.9 hours in group-I and 25.4±4.5 hours in group-II. The mean postoperative pain was 1.32±0.47 in group-I and 3.27±0.69 in group-II. 1(1.7%) patient had wound infection in group-II; however, no patients in group-I developed wound infection. The mean duration of hospital stay was 2.20±0.40 days in group-I and 3.62±0.98 days in group-II. The majority (81.7%) of the patients had the best quality of the scar in group-I and 48(80%) in group-II. The mean quality of the scar was 4.82±0.39 in group-I and 2.90±0.44 in group-II. All those differences except wound infection were statistically significant (P<0.001). This study demonstrated that laparoscopic appendectomy is as safe and effective as the open procedure. The overall benefit of laparoscopic appendectomy is more, as it results in less postoperative pain, shorter duration of hospital stays, better wound healing, as well as cosmetic outcome as compared to open procedure. CBMJ 2023 July: Vol. 12 No. 02 P: 157-163